Faktor-faktor yang Mempengaruhi Kualitas Hasil Pemeriksaan (Studi Empiris pada Inspektorat Kabupaten Bogor) - Adiguna, Mohamad; Satria, Arif; Suprayitno, Gendut (Jurnal Aplikasi Manajemen, 2015)
This research aimed to examine the influence of accountability, proficiency, independence, act upon code of ethics, due professional care, and vision, mission, goal, authority, and responsibility of quality of audit result at regional inspectorate officers. Common problems in this research are the existence of audit findings that are not detected by Inspektorat Kabupaten Bogor as an internal auditor. The populations of this research are auditors, the sampling technique using total sampling to 47 auditors. Data were analyzed using multiple linear regression analysis consist of t test, F test, and coefficient of determination.The results showed that the accountability, proficiency, and independence have a positive and significant impact on quality of audit result, while the variables act upon code of ethics, due professional care, and vision, mission, goal, authority, and responsibility do not have a significant impact on quality of audit result. Value of the coefficient of determination indicates that together the accountability, proficiency, independence, act upon code of ethics, due professional care, and vision, mission, goal, authority, and responsibility contribute to the dependent variable (quality of audit result) of 77.00%, while the remaining 23.00% are influenced by other outside factors model. Impacts of these findings is need for providing standard code of ethics for the auditor at the organization.